Application of the hydrological model chain of the RODOS decision support system for nuclear emergencies to the analysis of possible consequences of severe accident. (August 2023) - Pylypenko, O.; Bezhenar, R.; Kivva, S.; Kopka, P.; Potempski, S.; Wojciechowicz, H.; Zheleznyak, M.
Abstract: The paper deals with the implementation of the full hydrological model chain for the area where the first Polish nuclear power plant is to be constructed. One of the tasks to be performed is to estimate possible concentration of radioisotopes and doses, both during normal operation of the nuclear power plant and in case of accidental releases to the environment, in particular, including severe accidents. In the case of surface waters, the contamination can result from the release into the atmosphere, deposition, transport in the whole catchment system, and finally into the sea. Therefore an integrated approach has been applied for the implementation of the hydrological model chain in the RODOS system, starting from atmospheric dispersion, through the transport and dispersion of contamination in the catchment basin, which includes rivers and big lake, up to the sea and in coastal waters. Finally dose calculations have been performed. Highlights: Analysis for aquatic pathway in the case of releases of radioactive substance. The hydrological model chain of the RODOS decision support system. Approach to the analysis of transport of radioactive contamination in water bodies.